Bacterial diversity and successional patterns during biofilm formation on freshly exposed basalt surfaces at diffuse-flow deep-sea vents - Lara K. Gulmann (Frontiers in Microbiology, 2015)
Many deep-sea hydrothermal vent systems are regularly impacted by volcanic eruptions, leaving fresh basalt where abundant animal and microbial communities once thrived. After an eruption, microbial biofilms are often the first visible evidence of biotic re-colonization. The present study is the first to investigate microbial colonization of newly exposed basalt surfaces in the context of vent fluid chemistry over an extended period of time (4 to 293 days) by deploying basalt blocks within an established diffuse-flow vent at the 9o50’N vent field on the East Pacific Rise (EPR). Additionally, samples obtained after a recent eruption at the same vent field allowed for comparison between experimental results and those from natural microbial re-colonization. Over 9 months, the community changed from being composed almost exclusively of Epsilonproteobacteria to a more diverse assemblage, corresponding with a potential expansion of metabolic capabilities. The process of biofilm formation appears to generate similar surface-associated communities within and across sites by selecting for a subset of fluid-associated microbes, via species sorting. Furthermore, the high incidence of shared operational taxonomic units (OTUs) over time and across different vent sites suggests that the microbial communities colonizing new surfaces at diffuse-flow vent sites might follow a predictable successional pattern.